1993
DOI: 10.1038/hdy.1993.150
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and intra-plant SC length variation in Crepis capillaris

Abstract: Synaptonemal complexes (SCs) were measured in large samples (16-31) of pachytene nuclei from five different plants of Crepis capillaris, with the aim of conducting a systematic study of intra-plant and interplant SC length variation. Individual plants showed considerable variation in SC length among cells (average range= 1.83x), which is presumed to reflect stage-related differences in chromosome and SC length during pachytene. The five plants selected for study showed highly significant differences in SC leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
(8 reference statements)
1
3
0
Order By: Relevance
“…Our results suggest that there are genotypic effects on pairing and recombination in these Hordeum hybrids, as has been found in several other grass species hybrid combinations (DOVER and RILEY 1972;EVANS and AUNG 1985). A positive relationship between SC length and chiasma/recombination frequency has been reported previously in many species (BOJKO 1983(BOJKO , 1985JONES and CROFT 1989;DE AZKUE and JONES 1993;QUEVEDO et al 1997). The hybrids used in the present study, 102C2 and 103K5, have been shown to have mean recombination frequencies of 0.53 and 0.33 per pollen mother cell, respectively (ZHANG et al 1999) and now, a 32 % difference in SC length.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Our results suggest that there are genotypic effects on pairing and recombination in these Hordeum hybrids, as has been found in several other grass species hybrid combinations (DOVER and RILEY 1972;EVANS and AUNG 1985). A positive relationship between SC length and chiasma/recombination frequency has been reported previously in many species (BOJKO 1983(BOJKO , 1985JONES and CROFT 1989;DE AZKUE and JONES 1993;QUEVEDO et al 1997). The hybrids used in the present study, 102C2 and 103K5, have been shown to have mean recombination frequencies of 0.53 and 0.33 per pollen mother cell, respectively (ZHANG et al 1999) and now, a 32 % difference in SC length.…”
Section: Discussionsupporting
confidence: 86%
“…The present study shows an almost two‐fold variation in SC length between the two parental species, H. vulgare and H. bulbosum , and also between the two different interspecific hybrid combinations. It is possible that part of this variation may be due to sampling cells at different stages of pachytene, however, the relationship between pachytene stage and SC length is not clear‐cut and there is no uniform pattern of reduction in length in later pachytene stages (M oses et al 1977; A nderson et al 1985; D e A zkue and J ones 1993). In Hordeum , as in several other plant groups, it is not possible to identify the sub‐stages of pachytene but as our measurements were made on cells prepared from many florets on several occasions they represent a reasonable sample of any intraspecific variation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In all these cases, whatever the cause, higher chiasma/crossover frequencies are associated with longer SCs. An indication of the same relationship was found in wild population plants of Crepis capillaris, which was not dependent on sex difference or the presence of additional heterochromatin (de Azkue & Jones, 1993), but this conclusion was very tentative because of the low number of plants included in the study. It therefore remains a priority to determine whether this relationship does obtain in 'normal' individuals, independently of any special effects such as sex difference or possession of heterochromatin.…”
mentioning
confidence: 53%